Hepatitis C Virus E2 Envelope Glycoprotein Induces an Immunoregulatory Phenotype in Macrophages. Issue 5 (24th May 2018) - Kwon, Young‐Chan; Meyer, Keith; Peng, Guangyong; Chatterjee, Soumya; Hoft, Daniel F.; Ray, Ranjit
Abstract : A comprehensive strategy to control hepatitis C virus (HCV) infection needs a vaccine. Our phase I study with recombinant HCV E1/E2 envelope glycoprotein (EnvGPs) as a candidate vaccine did not induce a strong immune response in volunteers. We analyzed the interactions of HCV EnvGPs with human monocyte‐derived macrophages as antigen‐presenting cells. HCV E2 induced immune regulatory cytokine interleukin (IL)‐10 and soluble CD163 (sCD163) protein expression in macrophages from 7 of 9 blood donors tested. Furthermore, HCV E2 enhanced Stat3 and suppressed Stat1 activation, reflecting macrophage polarization toward M2 phenotype. E2‐associated macrophage polarization appeared to be dependent of its interaction with CD81 leading endothelial growth factor receptor (EGFR) activation. Additionally, E2 suppressed the expression of C3 complement, similar to HCV‐exposed dendritic cells (DCs), implying potential impairment of immune cell priming. Conclusion: Our results suggest that E2 EnvGP may not be an ideal candidate for HCV vaccine development, and discrete domains within E2 may prove to be more capable of elliciting a protective immune response. (Hepatology 2018).